Analisis Pengaruh Manajemen Laba dan Asimetri Informasi Terhadap Perusahaan Consumer Goods Cost of Equity - Ade Onny Siagian (CV. Syntax Corporation Indonesia, 2021)
The company will conduct profit management with the aim to meet its personal interests and sometimes there is a relationship between the agent and the company so that the agent will participate in profit manipulation so that investors want to invest in the company and for investors who use the services of agents, if they fully trust the agent then the investor will want to invest in the company suggested by the agent, But with a high enough profit, investors will ask for a greater rate of return than usual. Therefore, management certainly chooses to beautify financial statements by maintaining their profits while investors want a large dividend from the company so that this difference in interest triggers profit management practices. The purpose of this study is to find out the effect of profit management and information asymptomatic on the cost of equity. This quantitative research uses secondary data and with sampling methods in the form of purposive sampling obtained by 100 consumer goods companies registered with the IDX from 2015-2019 as samples. Processing data analysis using SPSS software version 23. The results showed that profit management and information asymmetry partially had no significant effect on the cost of equity. Likewise, it also jointly shows that profit management and information asymmetry have no significant effect on the cost of equity